PENGARUH INDEPENDENSI, KOMPETENSI, AKUNTABILITAS, DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT (Studi Pada Auditor Kantor Akuntan Publik Kota Semarang) - Yuni Listiani, 14.05.52.0153; Lisiantara, G. Anggana (Students' Journal of Accounting and Banking, 2018)
This study is intended to identify the impact of independence, competence, accountability, and time budget pressure on audit quality. This study was conducted at Public Accounting Firm (KAP) of Semarang city. Population in this research is auditor working at Public Accounting Firm (KAP) in Semarang City. Sampling was done by using convenience sampling method and the number of samples were 53 respondents. The primary data retrieval method used is questionnaire method. And data analysis using multiple linear regression model. the results of this study show that independence, competence, and accountability have a significant positive effect on audit quality, while time budget pressure has no effect on audit quality. Keywords: Independence, competence, accountability, time budget pressure and audit qualit